الإشارة الحسية في الأحاديث النبوية دراسة في ضوء علم اللغة - اسماعيل علي, عباس محمد (Gezira Journal of Educational Sciences and Humanities, 2026)
لقيت لغة الإشارة الاهتمام الكبير من قبل علماء اللغة وعلم النفس، ذلك لمكانة الإشارة اللغوية من حيث التسهيل في التواصل اللغوي، والتوضيح المعرفي، تهدف الدراسة إلى البحث عن الإشارة الحسية في الأحاديث النبوية، والكشف عن دورها في الإيضاح والبيان، ومعرفة الحكمة من استخدامه (صلى الله عليه وسلم) الإشارة. اتبعت الدراسة المنهج الوصفي الاستقرائي الاستنباطي. توصلت الدراسة إلى عدد من النتائج والتوصيات، ومن النتائج: إنّ من قيمة الإشارة ربط المحسوس بالمعنوي بغرض الإيضاح والترسيخ، وإنّ استخدامه صلى الله عليه وسلم الإشارة في الأحاديث غرضه الإيضاح والبيان، وللإشارة الحسية دورها في الوصف الدقيق عن التقديرات والمماثلات كا(لسبابة والوسطى) للمقاربة، (فضم أصابعه) للمصاحبة وهكذا. توصي الدراسة بالاهتمام بالإشارة والكشف عن قيمتها ودورها الاجتماعي والتعليمي.   Sign language has received considerable attention from linguists and psychologists because of the crucial role it plays in facilitating linguistic communication and providing cognitive clarity. The study aimed at investigating sensory gestures in the Prophet hadiths, revealing the role they play in clarification and explanation, and uncovering the wisdom behind their use by the Prophet. The study followed the descriptive, inductive and deductive method. The most important findings are as follows: One of the values of gestures is to connect the tangible with the abstract for the purpose of clarification and reinforcement. Thus, the Prophet's used gestures in hadiths for the purpose of clarification and explanation. Sensory gestures (such as using index and middle fingers) play a crucial role in providing a precise description of estimations and analogies for the purpose of approximation. The Prophet, therefore, brought his fingers together to signify companionship, etc. The study recommends focusing on studying gestures, revealing their values and their social and learning roles.